Subretinal Hyperreflective Material (SHRM) as biomarker of activity in Exudative and Non- exudative inflammatory choroidal neovascularization. (2nd January 2023) - Arora, Atul; Agarwal, Aniruddha; Bansal, Reema; Katoch, Deeksha; Marchese, Alessandro; Aggarwal, Kanika; Agrawal, Rupesh; Gupta, Vishali
ABSTRACT: Aim: To analyze the structural features and therapeutic response in clinical and subclinical inflammatory choroidal neovascularization (i-CNV) detected inside subretinal hyperreflective material (SHRM) using swept-source optical coherence tomography (SS-OCT) and SS-OCT angiography (SS-OCTA). Methods: In this prospective interventional study, subjects with quiescent posterior uveitis presenting with SHRM on SS-OCT and CNV network on SS-OCTA were included. Subjects with intraretinal fluid/subretinal fluid (IRF/SRF) received intravitreal antivascular endothelial growth factor (anti-VEGF) injections, while those with no IRF/SRF either received treatment or observation for 6 months until they developed IRF/SRF or decrease in best-corrected visual acuity (BCVA)/metamorphopsia. Serial comparisons included SHRM width and height and intrinsic flow signal on OCTA. Results: 28 eyes of 22 subjects (12 males; mean age: 29.52 ± 12.56 years) were evaluated. Subjects with IRF/SRF at baseline (n = 6 eyes; termed as exudative iCNVs) receiving treatment showed significant improvement in BCVA ( p = .017), SHRM width/height and flow signal ( p < .05). Among eyes with no IRF/SRF (n = 22; termed as non-exudative iCNVs), 7 received treatment and showed significant improvement in SHRM parameters and BCVA ( p < .05). 4/15(26.67%) eyes that received no treatment developed IRF/SRF upon 6-month follow-up. Conclusion: SHRM may act as a useful biomarker to monitor activity and response to therapy in eyes with iCNV.